BEHIND THE CHANGE OF THE NATIONAL EXAMINATION POLICY IN INDONESIA - J. Jailani (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran)
This study aimed to ﬁnd out the mapping of diﬃculties in mathematics National Examination (NE) in Senior High School along with changes in NE policy in Indonesia in the last 10 years. Researcher conducted descriptive explorative analysis to ﬁnd out the scope of material, the absorption, and mapping the diﬃculties faced by students in mathematics. Data analysis carried out by examining the data of each material and indicators. It grouped into two, namely low (50%) and high absorption (≥ 50%). The results showed that the overall absorption of the NE had decreased signiﬁcantly over the past 5 years (2013 to 2017). There did not ﬁnd out of diﬃcult material before implementation of Curriculum 2013. However, the last 5 years (after the period of implementation Curriculum 2013) have found several diﬃculties. Moreover, since 2015, almost all the materials on mathematics NE were categorized as diﬃcult after the changing in the status of the NE (not a determinant factor of students’ graduation) and implementation the computer-based test. The diﬃcult materials were probability, geometry transformations, space geometry, calculus, circles, linear programs, and statistics. Generally, the diﬃculties were in narrative problem-solving questions or using real-world contexts. Also, the results showed non-cognitive impacts (students’ motivation) as the result of the  policy changing, especially the status and technical implementation of the NE